Countermeasures to encounter brain drain in China’s securities industry due to COVID-19 - Jiang Mengmeng; Jakaria Dasan; Ren Jie (Penerbit Universiti Malaysia Sabah, 2023)
Brain drain has overshadowed the management of the securities industry before COVID-19’s threat. Things were getting worst during the COVID-19 pandemic in which the development of the Securities Industry requires an immediate solution to brain drain to normalize the effect of the epidemic. However, it is found difficult to attract talents as many of them prefer to grab the opportunity out there as China is becoming a more innovative-driven economy. This paper analyzed the implication of brain drain in human resource management in the Securities Industry. Countermeasures were proposed to encounter the problem of turnover which saw the exit of talents. Among others, improving training mechanisms, applying reasonable performance appraisal methods, establishing fair and competitive salaries, creating a humanized atmosphere, and nurturing people-oriented corporate culture might improve the efficient management of human resources and strengthen back the Securities Industry.